Quality Control Limits for Broth Microdilution Susceptibility Tests of Ten Antifungal Agents - Barry, A. L. (American Society for Microbiology, 2000)
Broth microdilution susceptibility tests of Candida species have now been standardized by the National Committee for Clinical Laboratory Standards (NCCLS). An eight-laboratory collaborative study was carried out in order to document reproducibility of tests of Candida parapsilosis ATCC 22019 and Candida krusei ATCC 6258 by the NCCLS method. Replicate broth microdilution tests were used to define control limits for 24- and 48-h MICs of amphotericin B, flucytosine, fluconazole, voriconazole, ketoconazole, itraconazole, caspofungin (MK 0991), ravuconazole (BMS 207147), posaconazole (SCH 56592), and LY 303366.